Is Montreal Cognitive Assessment a valuable test for the differentiation of Alzheimer's disease, frontotemporal dementia, dementia with Lewy body, and vascular dementia? - Fatemeh Afrashteh; Mostafa Almasi-Dooghaee; Naser Kamyari; Rayan Rajabi; Hamid Reza Baradaran (Dementia & Neuropsychologia, 2024)
ABSTRACT Dementia is one of the growing diseases in the world and has different types based on its definition. The Montreal Cognitive Assessment (MoCA) test has been employed to screen patients with dementia, cognitive impairment, and disruption of daily activities. Objective: This study examined the diagnostic value of the total MoCA score and its subscores in differentiating Alzheimer's disease (AD), frontotemporal dementia (FTD), dementia with Lewy body (DLB), and vascular dementia (VaD). Methods: A total of 241 patients (AD=110, FTD=90, DLB=28, and VaD=13) and 59 healthy persons, who were referred to a dementia clinic with memory impairment in Firoozgar Hospital, were included in this study. MoCA tests were performed in all patients and normal persons. Results: By using the receiver operating characteristic (ROC) curve and measuring the area under the curve (AUC) for the total MoCA score in each group, AUC was 0.616, 0.681, 0.6117, and 0.583 for differentiating AD, FTD, DLB, and VaD patients, respectively. Among the groups, just the VaD group showed no significant usefulness in using the total MoCA score to differentiate it. To compare MoCA subscores, AD patients had higher scores in digit span, literal fluency, and abstraction but lower delayed recall scores compared with FTD patients. Conclusion: The total MoCA score and its subscores could not differentiate people with different types of dementia in the setting of screening.